KUALITAS ONDE-ONDE DENGAN SUBTITUSI TEPUNG KETAN HITAM - Aryesi Putri, Nadila; Andriani, Cici; Holinesti, Rahmi; Faridah, Anni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of black glutinous rice flour substitution on the quality of onde-onde in terms of shape, color, aroma, texture, and taste. The background of this study is based on the limited innovation in onde-onde made from black glutinous rice flour, even though black glutinous rice has a higher anthocyanin content and nutritional value compared to white glutinous rice. This study used an experimental method with a completely randomized design (CRD) consisting of four treatments, namely black glutinous rice flour substitution at 0% (X0), 25% (X1), 50% (X2), and 75% (X3), with three replicates. Data were obtained through organoleptic testing by three expert panelists on the aspects of shape, color, aroma, texture, and taste, and were then analyzed using analysis of variance (ANOVA). The results showed that the substitution of black glutinous rice flour had a significant effect on the color, aroma, texture, and characteristic taste of black glutinous rice, but did not significantly affect the shape and sweetness of the onde-onde. The higher the substitution of black glutinous rice flour, the stronger the resulting characteristic color and aroma, but the level of texture elasticity tended to decrease. The best treatment was obtained with a 50% substitution of black glutinous rice flour because it produced the best balance in terms of color, aroma, texture, and taste. These results indicate that black glutinous rice flour has the potential to be used as an innovative ingredient in traditional food products to enhance product value and appeal.